2020
DOI: 10.3390/jmse8060444
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sealing and Leakage Performance of the Subsea Collet Connector with Lens-Type Sealing Structure

Abstract: The contact mechanics model of the metal lens-type sealing gasket is established on the basis of Hertz theory on the macroscopical scale in this paper. The relationship among sealing width, contact pressure, and preload is solved. Based on the structural characteristics of the subsea collet connector, the self-locking characteristics are analyzed to determine the gain coefficient of the sealing structure for the loading thrust. On the microscopic scale, the contact characteristics of the turning lens-type seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In engineering, the contact compaction effect and the sealing pressure are connected through an experiment. The experiment found that there is a linear relationship between the sealing pressure and the contact stress, and defines the ratio of the average contact stress applied to the unit effective area to the internal pressure, which is called the gasket coefficient, which is expressed by m. When the material of the metal sealing gasket is Incoloy 825, the gasket coefficient m = 6.5 [23], namely: p = mp in (18) In Figure 5e, the theoretical calculation equation of contact sealing of the ideal calculation model of underwater clamp connector is obtained by combining Equations ( 10), ( 15), ( 16) and (18):…”
Section: Derivation Of Contact Sealing Theory Of Underwater Clamp Connectormentioning
confidence: 99%
See 3 more Smart Citations
“…In engineering, the contact compaction effect and the sealing pressure are connected through an experiment. The experiment found that there is a linear relationship between the sealing pressure and the contact stress, and defines the ratio of the average contact stress applied to the unit effective area to the internal pressure, which is called the gasket coefficient, which is expressed by m. When the material of the metal sealing gasket is Incoloy 825, the gasket coefficient m = 6.5 [23], namely: p = mp in (18) In Figure 5e, the theoretical calculation equation of contact sealing of the ideal calculation model of underwater clamp connector is obtained by combining Equations ( 10), ( 15), ( 16) and (18):…”
Section: Derivation Of Contact Sealing Theory Of Underwater Clamp Connectormentioning
confidence: 99%
“…The axial force acting on the sealing gasket only accounts for 4% to 8% of the axial force provided by the press. The error fluctuation of the test measurement data will amplify the F a error fluctuation obtained by Equation (23).…”
Section: Inner Cavity Pressure Sealing Testmentioning
confidence: 99%
See 2 more Smart Citations
“…5 This leads to high maintenance costs as well as oil and gas leakage if a DPC fails. 6 Therefore, reliability analysis has been the focus of structure design and maintenance for DPCs.…”
Section: Introductionmentioning
confidence: 99%